(untitled) - Rougeau, Sandy; Quidelleur, Xavier; Famin, Vincent; Michon, Laurent; Nauret, François; Rusquet, Anaïs; Di Muro, Andrea (Comptes Rendus. Géoscience, 2025)
Since the onset of Fani Maore submarine eruption, the volcanism of the Comoros Archipelago has gained renewed interest. Geochronological constraints have been recently obtained for Mohéli, Anjouan and Mayotte islands and nearby seamounts. Here we provide new groundmass K–Ar ages for Grande Comore. Along with major and trace element geochemistry and geomorphological analyses, these ages enable us to propose a three stages reconstruction of the island. The first, or M’Badjini stage, is much older than previously thought, with ages as old as 2.2 Ma. Following a period of quiescence and dismantling, the second phase occurred between 280 and 230 ka, probably on both La Grille and Karthala volcanoes. Then, volcanic activity resumed for a third phase from ca. 130 ka until present time. The Comoros geochronological database, updated with our new results, confirms that the construction history of the archipelago occurred as pulses and follows a northward propagation of volcanism (i.e. a widening of the volcanically active region).